Students’ Ability in Translating English Active and Passive Sentences Into Indonesian - Sholihin; Kurniawan (JURNAL PENDIDIKAN BAHASA, 2018)
The researcher described about there was one problem of this study namely: (1) how is the students ability in translating english active and passive sentences into indonesian. While the purpose of this study namely: to know the student s ability in translating english active and passive sentences into indonesian. The method used in the study was a descriptive method. While the subject of this study was the eleventh grade of SMA Negeri 2 Woha, the researcher used english test as an instrument in collecting the data, the type of test was essay. The researcher anlyzed the data was descriptive statistics namelyideal mean score and ideal standard deviation for measured students ability in translating english active and passive into indonesian. Based on the result of data used test was essay test, the test consisted of 15 items. The highest score was 13 and lowest was 8. The mean score was obtained in this examination was 10,96 and standar deviation was categories into average level. The result of discussion that students ability in translating english active and passive sentences into indonesian was still in average level in translating english active and passive sentences. In can be conclue that can be more active in the translating class in which concern to get the high target in learning english translating achievement and the subject the other especially for translating active and passive sentence.